2013
DOI: 10.5194/isprsarchives-xl-1-w2-333-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accuracy of Dem Generation Algorithms From Uav Imagery

Abstract: Abstract. In this work we evaluated how the use of different positioning systems affects the accuracy of Digital Elevation Models (DEMs) generated from aerial imagery obtained with Unmanned Aerial Vehicles (UAVs). In this domain, state-of-the-art DEM generation algorithms suffer from typical errors obtained by GPS/INS devices in the position measurements associated with each picture obtained. The deviations from these measurements to real world positions are about meters. The experiments have been carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…As expected, indirectly geo-referenced imagery showed smaller residuals than the directly geo-referenced one. Horizontal RMSEs for indirectly geo-referenced imagery ranged from 0.058 to 0.089 m, whereas vertical RMSEs ranged from 0.046 to 0.075 m. In contrast to that, horizontal RMSEs for directly geo-referenced imagery ranged from 0.375 to 0.430 m, whereas vertical RMSEs ranged from 0.273 to 0.379 m. The accuracies of both methods are in accordance with the findings of Turner et al [55] and Ruiz et al [56], although vertical accuracy performs slightly better than expected. GCP-based accuracy assessment for directly geo-referenced imagery at Z39 and Z58 was not performed.…”
Section: Image Processingsupporting
confidence: 75%
“…As expected, indirectly geo-referenced imagery showed smaller residuals than the directly geo-referenced one. Horizontal RMSEs for indirectly geo-referenced imagery ranged from 0.058 to 0.089 m, whereas vertical RMSEs ranged from 0.046 to 0.075 m. In contrast to that, horizontal RMSEs for directly geo-referenced imagery ranged from 0.375 to 0.430 m, whereas vertical RMSEs ranged from 0.273 to 0.379 m. The accuracies of both methods are in accordance with the findings of Turner et al [55] and Ruiz et al [56], although vertical accuracy performs slightly better than expected. GCP-based accuracy assessment for directly geo-referenced imagery at Z39 and Z58 was not performed.…”
Section: Image Processingsupporting
confidence: 75%
“…The authors highlight issues with GPS accuracy as a main source of crop height error, as well as suggesting using higher quality cameras for image collection. Ruiz et al [33] also found the SfM algorithms suffer from errors present in GPS datasets. Ground-based Control Points (GCP) located within the scene are recommended as best-practice for spatial accuracy and minimisation of model error.…”
Section: Structure-from-motion and Crop Modellingmentioning
confidence: 99%
“…The quality of this model depends on many factors and parameters, such as the initial images quality, the availability of principal points and coordinates of vertical and horizontal control survey network points, flight altitude, overlaps and camera resolution. The final DSM accuracy is influenced by the variations of these factors and parameters (Ruiz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%